A EMBRAPA NO OESTE CATARINENSE: IMPLICAÇÕES DO PROGRAMA DE MELHORAMENTO GENÉTICO DE SUÍNOS (1975 - 1985) - Rossi, Handressa Louanne (2017)
The Brazilian Agricultural Research Company - EMBRAPA, has been at the forefront of the research on genetic improvement of pigs in Brazil, especially in the 1970s and 1980s, before large multinational companies entered the Brazilian market and practically covered all dominion over the main Genetic material of commercial importance. In this first moment, Embrapa finds a relatively organized market, but very much based on the importation of genetic material and not in the production of this material, fact of extreme importance for the agribusiness in great expansion in the country. It emerged as a way of incorporating the region into the current model of national development, its implementation was through the action of several specific groups, such as the Catarinense Association of Pig Breeders and Sadia. It is not by chance that this unit comes to the West of Santa Catarina, a space that has a great connection with the production of pigs / swine, the various ethnic groups that inhabit this space have relation with the creation, being fundamental for the maintenance, from the most humble families to great creators. Indigenous people, caboclos and immigrant settlers will, according to their needs and values, rename this production. Initially pigs were marketed especially for the production of lard, a process that underwent a major change in the period in question, with the expansion of the grain market, lard loses much space for vegetable oils, especially soybean oil. This process drives the need to shift from an animal that produces lard to an animal that produces as much meat as possible. Based on these assumptions, this research aims to analyze the space in which the Embrapa Swine and Poultry was inserted and how it was constructed, to construct a narrative about the meanderings of the researches in genetic improvement of swines that Embrapa will organize and produce in the Its first ten years of operation, to understand how the scientific factors are linked to political and economic issues of the time, as well as expose some consequences of the great growth and concentration of the population of pigs in the region. To achieve these objectives, documentary sources, technical reports, research reports and publications of Embrapa Pigs and Poultry in scientific or non-scientific vehicles are used. It can be seen at the end of this dissertation that scientific research, especially those of commercial interest, is being built by the combination of scientific and extra-scientific factors. In the 1970s and 1980s the preoccupations with the modernization of Brazil in a conservative way and its insertion in the international market is reflected in the research, just as in the 1990s international pressure, ecological movements and growing environmental concerns Provoke a great metamorphosis in the way the researches in the company are conducted.